Routes of Zika virus dissemination in the testis and epididymis of immunodeficient mice - Tsetsarkin, Konstantin A.; Maximova, Olga A.; Liu, Guangping; Kenney, Heather; Teterina, Natalia; Bloom, Marshall E.; Grabowski, Jeffrey M.; Mlera, Luwanika; Nagata, Bianca M.; Moore, Ian; Martens, Craig; Amaro-Carambot, Emerito; et al. (Nature communications, 2018)
Sexual transmission and persistence of Zika virus (ZIKV) in the male reproductive tract (MRT) poses new challenges for controlling virus outbreaks and developing live-attenuated vaccines. To elucidate routes of ZIKV dissemination in the MRT, we here generate microRNA-targeted ZIKV clones that lose the infectivity for (1) the cells inside seminiferous tubules of the testis, or (2) epithelial cells of the epididymis. We trace ZIKV dissemination in the MRT using an established mouse model of ZIKV pathogenesis. Our results support a model in which ZIKV infects the testis via a hematogenous route, while infection of the epididymis can occur via two routes: (1) hematogenous/lymphogenous and (2) excurrent testicular. Co-targeting of the ZIKV genome with brain-, testis-, and epididymis-specific microRNAs restricts virus infection of these organs, but does not affect virus-induced protective immunity in mice and monkeys. These defined alterations of ZIKV tropism represent a rational design of a safe live-attenuated ZIKV vaccine. The mechanisms of ZIKV persistence in the male reproductive tract (MRT) are poorly understood. Here, Tsetsarkin et al. applied microRNA-targeting approach to trace routes of ZIKV dissemination in the testis and epididymis and to generate immunogenic live-attenuated ZIKV vaccine candidate, restricted for MRT infection.